The impact of the system’s information base in improving the circulation of information and the quality of scientific research at Princess Noura bint Abdul Rahman University | أثر قاعدة معلومات المنظومة في الارتقاء بتداول المعلومات وجودة البحوث العلمية بجامعة الأميرة نورة بنت عبد الرحمن - Al Sawi | الصاوي , Yasser Mohamed Mohamed | ياسر محمد محمد; Al Haif | الهيف, Aalia Modakar Haif | عالية مذكر هيف (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
The study aimed to measure the impact of using Mandumah database on the circulation of information, and the use of research results in scientific research for faculty members from the employees of Princess Nourah bint Abdulrahman University, where the database is one of the most important bibliographicand full-text databases for studies and the work of conferences and university theses in the fields of education, humanities and forensic sciences issued in Arabic, where the study focused on measuring the impact of increasing the ability to complete research and studies from university employees, and the study also sought to evaluate The outputs of the database, whether they are bibliographic results used in reference citation, as well as in the form of scientific extracts or full-text results, and the evaluation also included lateral sorting factors for temporal and objective research results and other results related to the results, and the researchers were keen to apply the analytical survey study methodology, where the main measurement tool )questionnaire(was prepared, and the study sample included )258( members of the university’s faculty members who were randomly selected in humanitarian disciplines during the first semester )2022- 2023, 1443-1444H(, The study found that there is an increase in awareness among faculty members to use Mandumah database towards the completion of research and information circulation, and the use of its results in the teaching process to a high degree, and the study recommended the need for the university to pay attention t permanent connection to the Internet, and the need to hold training workshops for faculty members to use research systems and the need for adequate awareness of the information. | هدفت الدراسة إلى قياس أثر استخدام قاعدة معلومات المنظومة في تداول المعلومات، واستخدام نتائج البحث في البحوث العلمية لأعضاء هيئة التدريس من منسوبي جامعة الأميرة نورة بنت عبد الرحمن، إذ تعد قاعدة معلومات المنظومة إحدى أهم قواعد المعلومات الببليوجرافية وكاملة النص للدراسات وأعمال المؤتمرات والرسائل الجامعية في المجالًات التربوية والإنسانية والعلوم الشرعية الصادرة باللغة العربية. وقد ركزت الدراسة على قياس أثر زيادة القدرة في إنجاز البحوث والدراسات من منسوبي الجامعة، كما سعت الدراسة نحو تقييم مخرجات قاعدة المعلومات، سواء كانت نتائج ببليوجرافية تُستخدم في الًاستشهاد المرجعي، وكذلك على شكل مستخلصات علمية، أو نتائج كاملة النص. كما شمل التقييم عوامل الفرز الجانبي لنتائج البحث الزمنية والموضوعية والنتائج الأخرى المرتبطة بالنتائج، وحرص الباحثان على تطبيق منهج الدراسة المسحي التحليلي. وقد تم إعداد أداة القياس الرئيسة «الًاستبانة،» وشملت عينة الدراسة 258 عضوا من أعضاء هيئة التدريس بالجامعة تم اختيارهم عشوائيا في التخصصات الإنسانية، في خلال الفصل الدراسي الأول (2023-2022م/-1443 1444هـ.) وقد توصلت الدراسة إلى وجود زيادة في الوعي لدى أعضاء هيئة التدريس باستخدام قاعدة معلومات المنظومة في إنجاز البحوث وتداول المعلومات، واستخدام نتائجها في عملية التدريس بدرجة مرتفعة. وأوصت الدراسة بضرورة اهتمام الجامعة بالًاتصال الدائم بشبكة الإنترنت، وضرورة عقد ورش عمل تدريبية لأعضاء هيئة التدريس لًاستخدام أنظمة البحث، وضرورة التوعية الكافية بقاعدة المعلومات، مع الاستخدام الدائم لأساليب الًاستشهاد المرجعي العالمية.